26. THE CHARACTERISTICS OF CHILDREN WITH INVASIVE DISEASES CAUSED BY STREPTOCOCCUS PNEUMONIA IN CHILDREN’S HOSPITAL 1 (Vietnam Journal of Community Medicine, 2024)
Background: Streptococcus pneumonia is a common pathogen of pneumonia, bacteremia, and meningitis in children. Of which, invasive diseases caused by Streptococcus pneumoniae contributes to the increasing rate of morbidity and mortality, especically children younger than 5 years old. Is there difference between pneumococcal pneumonia and invasive pneumococcal disease?Objectives: The characteristics of children with invasive diseases caused by streptococcus pneumonia in Children’s Hospital 1.Methods: This research is a case series study in which disease cases are retrospectively recruited from January 2017 to July, 2022 and prospectively from July, 2022 to July, 2023.Results: Of the researched population, there are 76,8% of children aged 20mg/L (84,8%), anemia (56,1%), lobar pneumonia on X-ray (34,3%). Pneumococci is detected in blood in 81,8% while the figure for pleural fluid is modestly 10,1%. Common complications are pleural effusion (43,5%) and necrotizing pneumonia (19,2%). In our study, pneumococci is highly sensitive to vancomycin (100%), levofloxacin (88,9%), linezolid (100%). Invasive pneumococci have a high rate of resistance to macrolid (100%), sulfamid (77,8%), penicillin (20,2%). Most commonly used antibiotics during hospitalization are Cephalosporin 3rd generation. There are 96% of patients with improvement and recovery, while the mortality rate is 2%.Conclusions: Invasive pneumococcal pneumonia should be considered situations including clinical or laboratory complications, high fever with difficult breathing and poor feeding, or cases with high CRP level (> 100) with associated anemia.
Keywords: Invasive pneumococcal infection; Pneumococcal pneumonia; children; S. pneumoniae